Pharmaceutical company payments to authors of the Japanese guidelines for the management of hypertension. Issue 12 (26th March 2021) - Senoo, Yuki; Saito, Hiroaki; Ozaki, Akihiko; Sawano, Toyoaki; Shimada, Yuki; Yamamoto, Kana; Suzuki, Yosuke; Tanimoto, Tetsuya
Abstract : Abstract: Antihypertensive drugs have been of significant interest to the pharmaceutical industry due to increasing sales opportunities in a global market. The financial relationships between pharmaceutical companies and the Japanese Society of Hypertension (JSH) have a possible influence on clinical practices in Japan. This study examined the distribution of pharmaceutical payments made to the authors of the revised Guidelines for the Management of Hypertension (JSH2019) and the transparency of the Conflict of Interest disclosure that each author made. We retrospectively obtained publicly available data regarding payments made by Japanese pharmaceutical companies to all authors of the JSH2019 in 2016. We also collected data on individual financial disclosure of JSH2019 authors to investigate whether their self-reported financial relationship with companies were compliant to the financial disclosure policy of JSH2019. The total and mean payment values reported by pharmaceutical companies were $4, 246, 436 and $21, 447, respectively. Of the 198 authors, 171 (86.4%) authors received at least 1 payment. Of 74 authors required to disclose their conflict of interest (COI) the authors, one-third failed to follow the COI policy covering the clinical guidelines. Major pharmaceutical companies selling antihypertensive drug products in the Japanese market had a significant financial connection with the JSH2019 authors. Financial relationships between pharmaceutical companies and authors or Japanese medical societies are raising significant concerns about the credibility of clinical guidelines and the potentially biases and undue influences that they may cause, especially with respect to adverse prescription patterns.